Development of scanning electron microscope-compatible multiaxial miniature testing system. (12th August 2019) - Rahman, Farhan; Ngaile, Gracious; Hassan, Tasnim
Abstract: Knowledge of deformation and failure mechanisms at micro- to nano-length scales is important for the prediction of material behavior as well as the development of new materials with desired properties. In situ multiaxial testing with scanning electron microscopes (SEM) can reveal physical deformation mechanisms under realistic multiaxial loading conditions. Although in situ SEM testing has gained traction in recent years, there is currently no multiaxial in situ SEM testing stage available with axial-torsional loading capabilities which can generally be used in any SEM. In this study, we report the development of a multiaxial miniature testing system (MMTS) with a unique capability for performing axial-torsional testing of a tubular specimen with a 1–2 mm outer diameter, inside most SEMs. The different challenges of developing a multiaxial in situ SEM testing stage, such as small load frame size, appropriate specimen position, high vacuum compatibility of MMTS load frame components, as well as the development of installation accessories, were addressed. A custom SEM stage door was developed for the MMTS load frame. Verification tests have confirmed the successful development of the MMTS for in situ SEM testing. In addition, digital image correlation was used with recorded SEM images during the test to determine the surface strain.